Fostering Community Well-Being in Farming Practices - Francois, Jean R. (My University, 2023)
In recent years, there has been a growing recognition of agriculture’s critical role in promoting the well-being of both you [farmers] and your communities, which is a crucial outcome of many sustainability efforts. The role of agricultural producers extends beyond fields to support their livelihood and the well-being of their communities and their nation. Producers’ decisions and actions have, therefore, a profound and lasting impact on the well-being of their communities. This story map explores this interconnection of farming and community well-being and highlights key management decisions that farmers are consciously considering in their decision-making process. It also describes some potential benefits this agriculture– community relationship might have on both farm profitability and the overall well-being of agricultural communities. Through interviews with agricultural stakeholders, we gain valuable insights into practices and approaches that farmers across various regions in the U.S. are embracing to create a positive and sustainable impact on their communities.